Case report: Complete pathological admission in N3 unresectable locally advanced lung adenocarcinoma with a novel INTS10-ALK and EML4-ALK fusion after neoadjuvant crizotinib - Zhai, Xiaoqian; Wang, Ting; Lin, Yiyun; Zhang, Jiabi; Wang, Yuqing; Wang, Weiya; Zhou, Qinghua; Zhu, Daxing (Frontiers in Oncology, 2023)
Background Although anaplastic lymphoma kinase tyrosine kinase inhibitors (ALK-TKIs) have impressive response in advanced lung adenocarcinoma with anaplastic lymphoma kinase (ALK) fusion, no guidelines point to the potential benefits of neoadjuvant ALK-TKIs for N3 unresectable locally advanced lung cancer. Current ongoing clinical trials mainly focus on the efficacy of neoadjuvant ALK-TKIs in resectable locally advanced lung cancer and ignore the role of neoadjuvant ALK-TKIs in N3 unresectable locally advanced lung cancer. Materials and methods We report a lung cancer case with a novel INTS10-ALK and EML4-ALK rearrangement that achieved complete pathologic response to neoadjuvant crizotinib. We conducted molecular pathologic analysis by using next-generation sequencing (NGS). Genomic DNA was extracted from formalin-fixed paraffin-embedded (FFPE) samples and profiled using a capture-based targeted sequencing panel consisting of 56 lung cancer-related genes. Results Our study reported a patient with stage IIIB-N3 lung adenocarcinoma with an unreported dual ALK rearrangement (INTS10-ALK and EML4-ALK) who received 5 months of crizotinib, followed by R0 right upper lobectomy, achieving complete pathological response (ypT0 ypN0). No recurrence of the tumor was found for 3 years postoperatively. Conclusion The case supports the strategy of neoadjuvant ALK inhibitors for N3 unresectable locally advanced lung cancer, expanding the spectrum of treatment of stage IIIB-N3 lung cancer.